Multislice computed tomography in the diagnosis of orbital fractures - O. Yu. Pavlova; N. S. Serova (Вестник рентгенологии и радиологии)
Objective: to improve radiodiagnosis of orbital fractures at pre- and postoperative treatment stages, to provide a rationale for detailed evaluation of orbital osseous and soft tissue structures to prevent early postoperative complications.Material and methods. The I.M. Sechenov First Moscow State   Medical University Clinic examined 52 (100%) patients on days 1–2 after injury. A patient group consisted of 49 (94%) men and 3 (6%) women whose age was 17 to 49 years. Multislice computed tomography (MSCT) was carried out prior to surgery on the day of their admission. Postoperative MSCT was done within 7–10 days after surgical treatment.Results. Preoperative MSCT could reveal fractures of the inferior and lateral orbital walls in all 52 (100%) patients. Fractures of the medial and superior orbital walls were identified in 8 (15%) and 3 (6%) cases, respectively. In 12 (23%) patients, prolapse of the fat and oculomotor muscles into the respective maxillary sinus was imaged, which gave rise to enophthalmos and an increase in orbital volume. Three (6%) patients were identified as having sequels of   eyeball trauma. Optic nerve abnormality was detected in 11 (21%) patients. Oculomotor muscle injury was encountered in 20 (38%) patients. After surgical treatment, 4 (8%) patients had a persistent inferior orbital wall defect in the posterior portions where the retrobulbar fat prolapsed into the maxillary sinus. Three (6%) out of the 20 (38%) patients with different oculomotor abnormalities had persistent postoperative muscle injuries that were mainly associated with erroneous orbital floor implantation. The number of patients with eyeball disease remained unchanged – 3 (6%). Among 11 (21%) patients with a postoperative pathologically changed tortuous nerve course, the optic nerve attained its correct even course all the way in 5 (10%) cases; it remained pathologically changed as before in 6 (12%) cases.Conclusion. MSCT is the preoperative technique of choice for examining patients with orbital injuries. After surgery, MSCT in the early postoperative period makes it possible to assess the results of treatment and to reveal possible complications and it is a decisive guide for a doctor in charge when planning resurgery.